Motor Imagery Experiment Using BCI: An Educational Technology Approach - Ortiz Daza, Camilo Andrés; Simanca Herrera, Fredys Alberto; Blanco Garrido, Fabian; Burgos, Daniel (Lecture Notes in Educational Technology, 2020)
Three individuals participated in the experiment in a medical simulation lab at Bogotá’s Antonio Nariño University. The objective was to compare the power spectral densities of signals obtained with a brain-computer interface (BCI) using a Nautilus g.tec 32, for activities that constitute motor imagination of closing the right and left hand, implementing a protocol designed by the author. The methodology used is closely connected to BCI-based HCIs with educational application. The results obtained indicate a clear intergroup difference in the levels of power spectrum, and a similarity in the intragroup levels. Measuring the signals of cognitive processes in the frontal and parietal cortex is recommended for educational applications. Among the conclusions, we highlight the importance of signal treatment, the differences encountered in spectrum comparison, and the applicability of the technology in education.
Keywords: brain-computer interface; motor imagination; digital filters; power spectral density; analysis of variance; education; Scopus(2)